Assessing Teaching Competencies in Pre-Service Teachers: Design and Validation of INDUCTEACHING Instrument - Olmos-Rueda, Patricia; Violant-Holz, Verónica; Díaz-Vicario, Anna (Journal of Teaching and Learning, 2026)
Induction is a priority action during initial teacher training. This period should include formative training and assessment that allows the student teacher to reflect on their progress and the acquisition of teaching skills. This article presents the design (following a descriptive-inferential method of quantitative approach) and validation of the self-assessment instrument for teaching competencies INDUCTEACHING, developed ad hoc, within the framework of an induction proposal, with the participation of 19 education professionals - nine teachers from five universities who teach teacher training courses for preschool, primary and secondary school teachers and 10 teachers from six public schools - and a pilot test of the tool (in pre and post phases) with the participation of nine teachers in training in the last year of the Primary Education Degree during their training practices. The results demonstrate the tool's content validity and internal consistency and indicate an improvement in perceived mastery of competency between the pre- and post-phases, particularly in the analysis and reflection dimensions. It is observed that induction processes improve professional teaching skills and that the INDUCTEACHING self-assessment tool is useful for teachers in training to reflect on their skill acquisition.